Prognostic significance for recurrence of fibroblast growth factor receptor 2 in intrahepatic cholangiocarcinoma patients undergoing curative hepatic resection. Issue 5 (9th January 2023) - Toshida, Katsuya; Itoh, Shinji; Yugawa, Kyohei; Kosai, Yukiko; Tomino, Takahiro; Yoshiya, Shohei; Nagao, Yoshihiro; Kayashima, Hiroto; Harada, Noboru; Kohashi, Kenichi; Oda, Yoshinao; Yoshizumi, Tomoharu
Abstract: Aims: The fibroblast growth factor receptor 2 ( FGFR2 ) fusion gene is frequently found as a genetic abnormality in the FGFR pathway in patients with intrahepatic cholangiocarcinoma (ICC). The FGFR fusion protein, produced from the FGFR fusion gene, is thought to cause tumor cell growth. To date, there have been few reports on the relationship between pathologic FGFR2 expression and prognosis in patients who have undergone hepatectomy for ICC, and on the relationship between FGFR2 and tumor‐infiltrating lymphocytes (TILs). Methods and Results: We enrolled 92 patients who underwent hepatectomy for ICC and performed immunohistochemical staining for FGFR2 and cluster of differentiation 8, and hematoxylin and eosin staining for evaluating TILSs. The relationships between the FGFR2 and clinicopathological characteristics and outcomes were analyzed, and patients were classified into positive ( n  = 18) and negative ( n  = 74) FGFR2 groups. The FGFR2‐positive group contained more men ( p  < 0.0001) and had lower serum albumin ( p  = 0.0355) and higher carcinoembryonic antigen ( p  = 0.0099). Furthermore, multivariable analyses revealed that the FGFR2‐positive group had worse disease‐free survival (DFS) ( p  = 0.0002). Multivariate analysis showed that the independent prognostic factors for DFS were maximum tumor size (≥5 cm) ( p  = 0.0011), tumor localization (perihilar type) ( p  = 0.0180), and FGFR2 positivity ( p  = 0.0029). There was no significant difference in TILs count between the two groups. Conclusion: We showed that FGFR2 high expression was an independent prognostic factor for recurrence of resected ICC.